Pengaruh Penerapan Model Problem Based Learning Berbantu Media Video Animasi Terhadap Hasil Belajar Subtema Bangga Terhadap Daerah Tempat Tinggalku - Febriani, Ulfah; Windiyani, Tustiyana; Anjaswuri, Fitri (UNIB Press, 2022)
This research is a quantitative research uses quasi experimental method. This research is motivated by the phenomenon of the low learning outcomes of fourth grade students at SDN Margajaya 4, Bogor City. This study aims to determine the effect of the Problem Based Learning model assisted by animated video media on the learning outcomes of the sub-theme proud of the area where I live in for grade 4 students at SDN Margajaya 4, Bogor City, Even Semester of the 2021/2022 Academic Year. The data analysis technique used is the analysis prerequisite test including the normality test, the homogeneity of variance, and the research hypothesis test using the t test. The N-Gain calculation of Problem Based Learning model assisted by animated video media is 76 with 90.92% completeness learning outcomes, the N-Gain value of the conventional model is 49 with 75% completeness learning outcomes. The results of hypothesis testing show that tcount (7.80798) > ttable (1.99834), then H0 is rejected and Ha is accepted. So it can be concluded that there is an influence on the application of Problem Based Learning model assisted by animated video media on the learning outcomes of the sub-theme proud of the area where I live.